2010
DOI: 10.1523/jneurosci.4436-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Alzheimer's Disease β-Amyloid Deposition in Transgenic Mice ExpressingS-Palmitoylation-Deficient APH1aL and Nicastrin

Abstract: Sequential cleavage of amyloid precursor protein by ␤-and ␥-secretases generates ␤-amyloid peptides (A␤), which accumulate in the brains of patients with Alzheimer's disease. We recently identified S-palmitoylation of two ␥-secretase subunits, APH1 and nicastrin. S-Palmitoylation is an essential posttranslational modification for the proper trafficking and function of many neuronal proteins. In cultured cell lines, lack of S-palmitoylation causes instability of nascent APH1 and nicastrin but does not affect ␥-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 40 publications
1
28
1
Order By: Relevance
“…The pMX-C99 -6myc plasmid has been previously described (34). Rabbit polyclonal antisera against STIM1, APP, PS1, and Flotillin-2 were previously generated in our laboratory and have been described (35)(36)(37)(38). The following antibodies were purchased: anti-Nicastrin (Santa Cruz), mAb 9E10 (ATCC), anti-protein disulfide isomerase (Stressgen), and mAb 4G8 (Covance).…”
Section: Methodsmentioning
confidence: 99%
“…The pMX-C99 -6myc plasmid has been previously described (34). Rabbit polyclonal antisera against STIM1, APP, PS1, and Flotillin-2 were previously generated in our laboratory and have been described (35)(36)(37)(38). The following antibodies were purchased: anti-Nicastrin (Santa Cruz), mAb 9E10 (ATCC), anti-protein disulfide isomerase (Stressgen), and mAb 4G8 (Covance).…”
Section: Methodsmentioning
confidence: 99%
“…APH1aL and nicastrin in the forebrain and found that palmitoylation deficiency did not affect the ability of APH1aL, an isoform of APH-1 and nicastrin to form enzymatically active γ-secretase complexes [164]. However, interestingly, the transgenic mice co-expressing palmitoylationdeficient APH1aL and nicastrin exhibited a significant but moderate reduction of amyloid deposits in the forebrain and a lower level of insoluble Aβ, indicating a potential role of γ-secretase palmitoylation in the modulation of Aβ deposition in the brain.…”
Section: γ-Secretase Complex Palmitoylation and App Processingmentioning
confidence: 98%
“…Rabbit polyclonal antisera against STC2, GRP78, and flotillin-2 have been described previously (18,23,34). Rabbit antiserum CT11 reacts with the residues RFLEERP.…”
Section: Production Of Stc2mentioning
confidence: 99%